Interpreting welfare and relief in the Middle East - Naguib, Nefissa, 1960-; Okkenhaug, Inger Marie (Social, economic, and political studies of the Middle East, 2008)
Based on different problematic and methodological perspectives and sources, this book examines different involvements in welfare activities not only as contextualised in stable communities and nations, but also as they emerge in vulnerable states and disintegrating societies.